Infant learning platform using Arduino - Teh, Joo Han (Nanyang Technological University, 2020)
Infants are born ready to learn and they need to be in an environment where a variety of stimulating activities are available to give them lots of chances to learn and play. Play is fun and it gives your child a time to explore, observe, solve, practise and learn from mistakes. Shapes and colours are an essential part of early childhood education. The ability to identify shapes and colours can be used as an indicator and an accomplishment of a milestone in a child’s cognitive development. Before the days of mobile devices and computers, toys are one of the main sources of entertainment for infants. To this day, toys are still widely used all around the world. Choosing the right toy for your child is important because toys which are suited to the child’s age, abilities, and interests are effective for their development [10]. However, shopping for a new toy can be intimidating. Today, there is still a wide array of infant toys in stores. For example, there are shape sorters, toy cars, musical toys et cetera. Thus, it is important to assess your child’s ability or milestone before choosing the correct type of toys for him or her to play. This final year project report aims to point out the importance of infant learning in the area of shape and colour recognition. Furthermore, the project aims to design and build a prototype that makes use of shapes and colours to create a fun and engaging activity which is suitable for infants to play.